2013
DOI: 10.1109/tmi.2013.2275233
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Operative 2-D Ultrasound and Dynamic 3-D Aortic Model Registration for Magnetic Navigation of Transcatheter Aortic Valve Implantation

Abstract: We propose a navigation system for transcatheter aortic valve implantation that employs a magnetic tracking system (MTS) along with a dynamic aortic model and intra-operative ultrasound (US) images. This work is motivated by the desire of our cardiology and cardiac surgical colleagues to minimize or eliminate the use of radiation in the interventional suite or operating room. The dynamic 3-D aortic model is constructed from a preoperative 4-D computed tomography dataset that is animated in synchrony with the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Normalized mutual information (NMI) is a method used to measure the correlation between two sample sets based on the joint entropy, namely, the transmission of information is acquired from an observation of sample A to the knowledge of sample B [ 34 , 35 ]. The principle of MI is outlined as follows: …”
Section: Methodsmentioning
confidence: 99%
“…Normalized mutual information (NMI) is a method used to measure the correlation between two sample sets based on the joint entropy, namely, the transmission of information is acquired from an observation of sample A to the knowledge of sample B [ 34 , 35 ]. The principle of MI is outlined as follows: …”
Section: Methodsmentioning
confidence: 99%
“…For validation, we compared the performance of our approach against the gold standard, using data from nine patients, each having 35 AV US images, and demonstrated that out method can segment the AV effectively. We believe the shape-constraint GCV approach can play an important role in image guided TAVI intervention 41 and computer-aided diagnoses of cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…In Ref. [ 16 ], the researchers registered intra-operative US images with a dynamic aortic model to improve the performances of a magnetic tracking system. The construction of the dynamic 3D aortic model leverages a pre-operative 4D CT dataset.…”
Section: The State-of-the-art In Multimodality Registrationmentioning
confidence: 99%